Magnitude of Anemia and Associated Factors among Pregnant Women Attending Antenatal Care in Public Hospitals of Ilu Abba Bora Zone, South West Ethiopia: A Cross-Sectional Study - Adamu Kenea; Efrem Negash; Lemi Bacha; Negash Wakgari (Anemia)
Background. Anemia is a global public health problem affecting all population particularly pregnant women. Hence, this study assessed the magnitude of anemia and associated factors among pregnant. Methods. Institution based cross-sectional study was conducted among 416 pregnant women attending antenatal clinic in three public hospitals of Ilu Aba Bora zone. The study participants were selected by proportional allocation based on the number of pregnant women that the respective health facilities contain. Semistructured questionnaire was used for data collection. Midupper arm circumference was employed to assess the nutritional status and standard mood depression assessment tool was used to assess depression. Data were centered and analyzed using SPSS version 20.0. Logistic regression analyses were used to see the association of different variables. Results. In this study, 31.5% of pregnant women were anemic. In addition, having family size five and above [AOR = 2.97, 95% CI (1.69, 5.27)], being rural resident [AOR=2.74, (95%CI) (2.11, 5.06)], had a higher odds of anemia. Similarly, having soil transmitted helminthes infection [AOR= 3.19, 95% CI (1.5, 6.65)] and history of malaria infection in the last one year [AOR= 3.10, 95% CI (2.10, 5.06)] had also a higher odds anemia during pregnancy. Moreover, being undernourished [AOR= 2.74 95% CI (1.34, 5.57)] was negatively associated with magnitude of anemia. Conclusions. The magnitude of anemia among pregnant women was found to be significant. Residence, family sizes, history of malaria infection during the last one year, and undernourishment were significantly associated with anemia during pregnancy.